Heterogeneous impact of internet availability on female labour market outcomes in an emerging economy: Evidence from Indonesia - Niken Kusumawardhani; Rezanti Pramana; Nurmala Saputri; Daniel Suryadarma (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Greater female labour market participation has important positive implications not only for women's empowerment and the well-being of their families but also for the economy they live in. In this paper, we examine the various effects of internet availability on women's labour market outcomes in Indonesia. As each worker subgroup tends to respond differently to changes in technology, examining the heterogeneity in the impact of internet availability on female labour market outcomes is central to our research. By constructing a district-level longitudinal dataset covering the period 2007-18, we find that internet availability has only a small significant effect on the female labour force participation rate and no statistically significant effect on the employment rate. However, internet availability increases the probability of women having a full-time job, especially for women aged 15-45 and those with a low level of education. Our study shows that internet availability does not always bring favourable labour market outcomes for women. We find that internet availability lowers the probability of women with a low level of education working in a high-skilled job and in the formal sector. Our results are robust to several robustness checks. Analysis of our qualitative interviews with a subsample of recent mothers supports the conclusion that the ability to be prepared for and attain flexible working conditions are two important values provided by the internet. We argue that a women-friendly working environment and adequate IT infrastructure are crucial elements in maximizing the role of the internet in helping women to achieve more favourable labour market outcomes.
Keywords: J16; O12; O33; 330; internet; labour market; Indonesia; female labour force participation